Lucas paradox and allocation puzzle: Is the euro area different? - Sabine Herrmann; Jörn Kleinert (Deutsche Bundesbank, 2014)
This paper examines the Lucas Paradox and the Allocation Puzzle of international capital flows referring to a panel data set of EMU countries and major industrialized and emerging economies. Overall, the results do not provide evidence in favour of the Lucas Paradox and the Allocation Puzzle. Rather, in line with neoclassical expectations, net capital flows are allocated according to income and growth differentials. The 'downhill' flow of capital from rich to poor economies was particularly pronounced in intra-euro area capital flows and after the introduction of the common currency. If we control for the fact that the assumptions of the neoclassical model are not perfectly given in emerging markets, the Lucas Paradox and the Allocation Puzzle can be dismissed for these countries too. However, in periods of financial stress, the neoclassical behaviour of financial flows is to some extent dampened.
Keywords: E22; F21; F36; O16; O57; 330; Financial integration; International Capital Flows; European Monetary Union